Impacts of Migration on Poverty Reduction: A Critical Analysis - Kunwar, Laxman Singh (Journal of Population and Development, 2021)
This paper attempts to describe impacts of migration on poverty reduction at individual, households, community and national level. Both internal and international migration phenomenon including working environment of migrants are analyzed. The paper is based on secondary sources of information with aim of find evidence on linkages between migration and poverty at individual, household and community and National levels. Migration phenomenon has shown the evidences of in reducing poverty level but migrants are being compelled to work in an exploitative and unhygienic environment. Female migrants are being more victims of exploitation than male migrants. The poverty reduction has been gained in return of exploitative and health hazards working environment of migrants can be considered as an injustice to migrants and their place of origin as well as countries of origin.